Synchronized Multimedia on Motivation and Academic Performance of Students - Nkweke, Obinna C; Dirisu, Chimezie N.G; Ndubuisi, Umesi (Mediterranean Journal of Social Sciences, 2012)
Multimedia [MM] materials and equipment are instructional materials which teachers and trainers use as alternativemeans of communication to transmit curriculum content to the learner. MM combines two or more different types of instructionalmaterials at the same time in a presentation. They have synchronization potentials and can be effectively used to facilitateteaching and learning process, arouse learners’ interest, support and reinforce students learning, influence better academicperformance in learners, aid mastery learning, among other things. This paper presents the results of research studies carriedout to determine the effect of synchronized MM use on motivation and academic performance of students in Biology. Pearsonproduct correlational analysis indicated lack of correlation between use of synchronize MM and students’ motivation while t-testindicates significant difference between biology students who were taught with synchronized MM (mean score, 51) and thecontrol group (mean score, 23). The control group who were taught the same Biology devoid of synchronized MM packageperformed poorly. We recommend that there is need for government to provide multimedia in secondary school and the biologyteachers to make transition to use modern MM devices and adopt different approaches for biology instruction and laboratoryactivities rather than the traditional or conventional talk-chalk method.